Tweencom girls : gender and adolescence in Disney and Nickelodeon sitcoms - Oppliger, Patrice A. (Children and youth in popular culture, 2019)
Banet-Weiser (2004) marked the debut of Clarissa Explains it All in 1991 as a crucial turning point for recognition of girls as "important empowered subjects in the social world." The current study of tweencoms focuses on the different ways character tropes are portrayed in media targeted to 8-12 year olds, particularly female characters, over the last 25 years. The focus is limited to the cable giants Disney Channel and Nickelodeon because of their popularity and high concentration of original programming targeted to tweens that airs nearly round-the-clock. This book employs a thematic analysis approach, similar to the one adopted by Riggs (2011) in his identification of the ways in which particular groups of characters are represented and the implications such representations might have for viewers. It incorporates cultivation theory (Gerbner 1998), which is based on media consumption's influence on distorted perceptions of reality, and social cognitive theory (Bandura 1986), which explains the relationship between vicarious exposure to specific behaviors and imitation of those behaviors. This book provides extensive examples and alternative interpretations of the shows' tropes and themes, particularly for those who are unfamiliar with the genre. Past research has shown that media and popular culture portrayals are influential for young viewers and yet live-action, cable comedies targeted to adolescents have gone relatively unnoticed. Much of the previous research has focused on very young girls and princess culture. The book is broken up into two sections. The first section explores common tweencom tropes. Subsequent chapters focusing on different themes that are prevalent throughout the series. The concluding chapter includes a discussion of the big picture of how the tropes and themes give insight into the female characters portrayed in the popular tweencom programming. The final chapter will also include advice to parents and educators.